Atuação do enfermeiro na segurança do paciente em ambiente hospitalar - Silva, Aline Teixeira (2016)
In the hospital context, a scenario of high complexity, safe practices are necessary and must permeate the nurses 'performance. The objective of this study was to analyze the nurses' performance, in terms of patient safety, in a hospital institution. Approved by the Ethics Committee of the Federal University of Alfenas, Opinion nº1.189.495. A qualitative study with an approach in Dialectical Hermeneutics, carried out with 42 nurses from a hospital institution in the South of Minas Gerais state. Data collection was performed in October 2015, using the semi-structured interview conducted by the guiding questions: "Tell me what you know about patient safety"; "Talk about what you perform as in everyday life of nurse in patient safety in the unit of action" and "Talk about any ideas or proposals you would have for patient safety at the facility." Three empirical categories were identified: patient safety and the ways of quality management in a hospital; Paths for the humanization of care in the hospital environment and the nurse's role in the hospital environment. The knowledge presented by the nurses corroborates with the definitions of the World Health Organization and the National Patient Safety Program in force in the country. The use of strategies, protocols, empathy, communication, permanent education and the participation of the companion were points raised by nurses as crucial for the strengthening of patient safety in the Institution. The hierarchy of functions and knowledge, overcrowding, overwork, bureaucratization of assistance and the lack of adhesion of the team were presented as obstacles to the expansion of a safety culture in the institution. It is considered that the praxis of the nurse in patient safety in the hospital environment is consolidated by the leadership in relation to the nursing team, by the exercise of management and assistance and by the interaction with the multi professional team, based on communication with a focus on light technologies And in the valuation of strategies for Continuing Education and for Permanent Education.